China’s Infrastructural Diplomacy in Africa - Agubamah, Edgar (Kashere Journal of Politics and International Relations, 2023)
Most African countries have poor level of infrastructural development which directly impacts negatively their economic growth. In response to ameliorate this anti-development deficiency, African governments have sought to engage various stakeholders in the development of infrastructure. China is not left out in this race to solve Africa’s infrastructural deficiency and her role in this direction in Africa has currently sparked attention both locally and internationally. It is against this backdrop that the work critically examined the motives or factors behind China’s infrastructural diplomacy in Africa. The study employed the economic nationalism theoretical framework and also made use of a secondary source of data anchored in documentary evidence in understanding China’s mode of infrastructural engagement in Africa. The work discovered economic considerations in terms of the search for raw materials. Natural resources and the need for a viable market influence China’s infrastructural diplomacy in Africa. Be that as it may, the study vehemently recommends that no matter the various reasons for China’s infrastructural diplomacy, African countries should key into the developmental projects that are been carried out by China and ensure that it is sustained for the overall development by the various countries within the continent. For clarity and easy comprehension, this study is segmented into seven sections:-introduction, background to China-African relations, theoretical framework, motivations for China’s infrastructural diplomacy in Africa, China’s infrastructural diplomacy in Africa, conclusion, and recommendations.